Bringing migrant domestic work literature into family studies: the intricate dynamics of au pair families - Pelechova, Lenka (2014)
This thesis explores families with live in au pairs. In particular, it investigates the changes that families go through as a result of the addition of an au pair, as well as the means by which the host parents and au pairs negotiate their new circumstances of living and working together. From a theoretical perspective, the thesis is positioned between two bodies of literature, namely, those of migrant domestic work and family studies. Up until now, research conducted in relation to au pairs has mostly been done as a part of feminisation of migration and domestic work divisions. However, such studies do not focus on the family as a unit of analysis and on the diverse experiences of different family members. In terms of family theories, there is a general consensus among scholars that contemporary families are diversifying. Even though the heterosexual couple family is still the most common form, new types of families are emerging, such as lone parents, divorced parents, same sex couples, extended families, reconstituted families, foster families and transnational families. Although the field of family studies has directed attention to diverse family forms, families with live in au pairs have, so far, escaped attention. The host families who employ and live with au pairs have to reset and renegotiate boundaries between fictive kin, family member and domestic worker. This thesis addresses the gaps that are present in much of the literature on migrant domestic work; namely the multifaceted relationships between host parents and au pairs, and the diversity of au pair’s experiences. The role of an ‘employer’ is approached not only from the viewpoint of migrant domestic work, but also from a family studies perspective. This focus allows for a greater understanding of family roles, family time and family boundaries and how they are re-negotiated by au pair employment. The exploration of au pair families was conducted through qualitative analysis consisting of semi structured interviews with 18 host parents and 19 au pairs. The data illustrate that host parents developed various and lengthy strategies to ensure that their au pairs were ‘the perfect fit for their family’. This commodified version of an ideal au pair was largely affected by the host parents’ social class position as well as by their ideals of ‘the family’. Moreover, the degree of association, communication, relationship and involvement with au pairs, appeared to be very different between host mothers and host fathers. In accordance with the gendered roles and division of work within families, the interviews with host mothers and host fathers revealed that the au pairs were perceived as mainly the host mother’s responsibility. Host parents’ endeavours in creating the ‘au pair family’ were explored through their negotiations of ‘family time’. ‘General family time’ consisted of sharing family related activities with the au pair while ‘genuine family time’ meant that the au pair was not involved. Although au pair families navigated their proximity by negotiating their family time and relationships which revealed that families are adaptable, at the same time these host families were crowded with images of the romanticized traditional family. The thesis claims that the combination of family and migrant domestic work scholarship enables a greater understanding of how living with and employing an au pair is experienced and managed in everyday life. Following these empirical findings, it is argued that whilst host families ‘displayed’ flexibility and fluidity (Beck 1992), at the same time, the hegemonic notions of what families should be like indicate that traditional values still prevailed.